Comparison of Mortality and 30-Day Complication Rates for Patients Undergoing Fixation versus Revision Arthroplasty after Periprosthetic Fractures of the Hip and Knee - Kouk, Shalen; Kester, Benjamin S.; Behery, Omar A.; Vigdorchik, Jonathan M.; Schwarzkopf, Ran (The Journal of Hip Surgery, 2018)
Periprosthetic fractures of the hip and knee are often associated with significant morbidity and mortality and may require operative fixation or revision arthroplasty to restore ambulation and functional status. There is scarce literature comparing patient profiles and operative complications between periprosthetic fractures of the hip/knee and the predisposing risk factors. The main study goal is to compare the postoperative complication rates and mortality between operative osteosynthesis fixation and revision arthroplasty while also evaluating the patient characteristics, intraoperative factors, and 30-day postoperative complications of periprosthetic total hip arthroplasty (THA) and total knee arthroplasty (TKA) fractures, as well as patient-related risk factors for serious adverse events. Patients who underwent surgery for periprosthetic fractures around a THA/TKA prosthesis were identified from the American College of Surgeons National Surgical Quality Improvement Program database between 2008 and 2015. Preoperative patient demographics and comorbidities, as well as operative factors and 30-day postoperative complications were compared between periprosthetic factures of the hip and those of the knee. A multivariable logistic regression analysis was used to identify patient risk factors for adverse events. Of 1,171 identified patients, patients with THA and TKA periprosthetic fractures had similar characteristics and were more likely female, with age over 70 years and a body mass index of > 25. Both groups had similar 30-day complication rates, with 9.8% of hip patients and 11.2% of knee patients having a postoperative complication. Mortality rate for THA periprosthetic fracture status postrevision or fixation was 3.6% and 3.3% for those with TKA periprosthetic fractures. There was no significant difference in 30-day mortality or postoperative complication rates in periprosthetic fractures treated with operative osteosynthesis fixation versus revision arthroplasty for THA and TKA. Patients with periprosthetic hip and knee arthroplasty fractures can be effectively managed with either operative osteosynthesis fixation or revision arthroplasty when properly indicated, with no significant difference in mortality, complication, or reoperation rates.
Keywords: Hip; knee; complications; risk factors; periprosthetic fractures